Jeff Garmany & Anthony Pereira (eds.) Understanding Contemporary Brazil - Matthew Webb (Brasiliana: Journal for Brazilian Studies, 2019)
In Understanding Contemporary Brazil, Jeff Garmany and Anthony W. Pereira have compiled a welcome and distinctly post-modern synthesis of contemporary scholarship on Brazil.